1990
DOI: 10.1002/art.1780330819
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of interleukin‐4 and high levels of transforming growth factor β in rheumatoid synovitis

Abstract: Since interleukin-4 (IL-4) displays agonistic effects on both T and B cells, we studied whether this lymphokine is involved in rheumatoid synovitis, a disease characterized by intense T cell infiltration and B cell stimulation. Rheumatoid arthritis synovial fluids (RA SF) contained no (<15 pg/ml) or very low amounts (C25 pg/ml) of IL-4, as measured by a sensitive and specific enzyme-linked immunosorbent assay. No IL-4 was produced by unstimulated rheumatoid synovial membrane. RA SF were found to inhibit phorbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(29 citation statements)
references
References 34 publications
1
26
0
2
Order By: Relevance
“…In addition, many women experience improvement of their arthritis during pregnancy (reviewed in [35]), and the switch towards a Th2 profile in pregnancy may be at least partially responsible [36]. Synovial fluid from patients with RA has shown either low or absent IL-4 [37], although Raza et al demonstrated a distinct cytokine profile in synovial fluid (SF) which included IL-4 [2]. In general, the chemokines and cytokines found to be elevated in our EIA cohort may represent an activated immune system, which continues during established RA, although there are likely to be treatment effects in patients with long-standing disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many women experience improvement of their arthritis during pregnancy (reviewed in [35]), and the switch towards a Th2 profile in pregnancy may be at least partially responsible [36]. Synovial fluid from patients with RA has shown either low or absent IL-4 [37], although Raza et al demonstrated a distinct cytokine profile in synovial fluid (SF) which included IL-4 [2]. In general, the chemokines and cytokines found to be elevated in our EIA cohort may represent an activated immune system, which continues during established RA, although there are likely to be treatment effects in patients with long-standing disease.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility would be that these anti-CCP-positive patients with psoriasis may have coexistent RA. Both psoriasis patients and RA patients are recognized to be Th1-associated diseases [28,29]. Furthermore, both diseases are sensitive to anti-tumor necrosis factor-alpha agents [30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In the current paradigm, although both Th1 and Th17 cells are described as contributing to RA pathogenesis [2,12,14], the role of Th1 cells is becoming controversial. In addition, the presence of IFN-g has been detected rarely in the synovial fluid of patients with RA [15,16]. Nevertheless, in established RA, IFN-g producing T cell clones have been found in synovial fluid and peripheral blood; hence, they indicate a Th1 phenotype [17].…”
Section: Introductionmentioning
confidence: 99%